Effect of silane coupling agent on flexural properties of fiber-reinforced geopolymer-cemented aeolian sand - Shuai Pang; Jiaze Li; Mengjie Li; Changzhi Zhao; Henghui Fan; Xiangdong Zhang (Case Studies in Construction Materials)
To enhance the flexural properties of polypropylene fiber (PPF)-reinforced geopolymer-bonded aeolian sand and increase the service life of trench backfill materials, this study improves the flexural performance by two methods: soaking fibers in a diluted silane coupling agent (KH570) solution of varying concentrations and directly adding KH570 during specimen preparation. The flexural behavior of the specimens under different conditions was tested using three-point bending tests. Additionally, digital image correlation (DIC) technology was employed to observe the progressive failure evolution of the specimens, and the mechanical parameter evolution was analysed. The mechanism of KH570 modification was revealed using scanning electron microscope (SEM) microanalysis. The results show that soaking the fibers in a 1.5 % KH570 diluted solution makes the fiber surface uniformly rough, increasing the specific surface area, which enhances the wrapping ability of the geopolymer-bonded aeolian sand around the fibers. In the three-point bending test, the maximum crack width was reduced by 54.96 %, the farthest crack extension was shortened by 6.80 mm, and the maximum generalized crack area decreased by 42.39 %. Incorporating 1.5 % KH570 into the specimens effectively improved the physico-chemical properties of the fiber-matrix interface, promoted product formation, and strengthened the interfacial bonding ability. As a result, the flexural performance of the specimens significantly improved. In the three-point bending test, the maximum crack width reduced by 0.64 mm, the farthest crack extension decreased by 10.56 mm, the crack area shrank by 9.37 mm², and the crack fractal dimension decreased by 0.132. During the failure process, with increasing load, the displacement field of the specimens gradually evolved from uniform deformation to localized non-uniformity. After reaching the peak load, significant changes were observed in the displacement field. The research findings have significant implications for the selection of pipeline backfill materials, their service life, and environmental protection.